«FUI, VI Y GOCÉ POR LAS CONQUISTAS DE LA RELIGIÓN Y DE LA CIENCIA»: Viajes y relatos de un obispo latinoamericano por Oriente (1885-1908) = "I WAS, SAW AND ENJOYED BY THE CONQUESTS OF RELIGION AND SCIENCE" : Travels and stories of a Latin American bishop in the East (1885-1908). - Hernández Méndez, Sebastián (Rivista di storia del cristianesimo, 2020)
The article studies Uruguayan bishop Mariano Soler's travels through the Middle East and the main works they gave rise to. Its purpose is to examine the intersections between orientalist representation and ultramontane discourse. It argues that these travels and texts respond to a «glocal» logic: the defense of Catholicism in the Río de la Plata and its globalization in Latin America. In this sense, the «global» and the «local» converge in Soler's works, making the Middle East a symbolic place from which to counter anti-clerical culture and reassert ultramontane Catholicism. Soler's experience allows a more profound understanding of the construction of an ultramontane imaginary in Latin America and its capacity to relate to other centers of reference beyond Rome.